2013
DOI: 10.4291/wjgp.v4.i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus positive ulcerative colitis: A single center experience and literature review

Abstract: Gancyclovir-treated patients had a more severe disease and outcome, probably unrelated to antiviral therapy. Immunohistochemistry-CMV-positive patients with mild disease may recover without antiviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…CMV may be transiently reactivated and disappear without antiviral therapy. In one study it was noted that those with more severe disease were more likely to be treated with ganciclovir, and were more likely to require either rescue therapy or surgery, despite adequate treatment of CMV . CMV colitis complicating UC leading to acute severe colitis can be challenging to manage.…”
Section: Aims and Methodsmentioning
confidence: 99%
“…CMV may be transiently reactivated and disappear without antiviral therapy. In one study it was noted that those with more severe disease were more likely to be treated with ganciclovir, and were more likely to require either rescue therapy or surgery, despite adequate treatment of CMV . CMV colitis complicating UC leading to acute severe colitis can be challenging to manage.…”
Section: Aims and Methodsmentioning
confidence: 99%
“…Systematic reviews in adults have proposed that anti-CMV treatment may be clinically effective in ASC but there is inconsistency regarding the method of defining CMV infection (64)(65)(66)(67). Recent guidelines report that intestinal CMV disease requires the presence of multiple inclusion bodies on histology and/or positive staining on immunohistochemistry rather than merely positive PCR (68)(69)(70)(71).…”
Section: Initial Managementmentioning
confidence: 99%
“…However, spontaneous recovery of acute CMV infection has been shown to occur in an immunocompetent patient with UC (21). Moreover, a recent study reported that mild CMV colitis in patients with UC was cured without antiviral therapy (31). Therefore, the use of antiviral agents for acute CMV infection superimposed on immunocompetent UC should be assessed carefully based on the patient's condition, including disease activity and clinical course.…”
Section: Discussionmentioning
confidence: 99%